A case study on sustainable business models of social enterprises in Visayas - Calantuan, Erine M (Animo Repository, 2021)
Social enterprises have continuously been gaining more attention over the years as the concepts and practices of corporate social responsibility and sustainability have been widely accepted by firms and society across the world. Studies show that social enterprises’ business models cater to economic, social, and environmental aspects along with having sustainable practices. This paper aims to understand the business model of social enterprises in Visayas as well as their sustainable practices through utilizing the Triple Layer Business Model Canvas (TLBMC) and Sustainable Consumption and Production (SCP) elements based on the descriptions and indicators or measurements by Tilley and Young (2006), Santiago (2013), Aure et al (2018), and Industry 4.0 elements from Cochran and Raunch (2020). Interviews with the social enterprises’ CEOs and/or co-founders made it possible to conduct a comprehensive cross case analysis on the three social enterprises based in Visayas namely AtoANI, Panublix, and BagoSphere. The researchers’ findings showed that AtoANI and Panublix have incorporated the triple bottom line in their business models, while BagoSphere has only taken into account the economic and social aspects. In light of these findings, the researchers have proposed recommendations for each social enterprise included in this study. For AtoANI and Panublix, the group recommends partnering with e-commerce platforms to sell their products so that these social enterprises can earn more revenue as well as expanding their market. For BagoSphere, it is recommended to measure the carbon footprint that the social enterprise produces in doing their business to provide alternative learning materials for its students.